Analisis Komponen Kamus Saluni Fil Mutaradifat Wal Ma’ani dalam Pembelajaran Bahasa Arab - Rohmawaty, Evy Nur; Anshory, Abdul Muntaqim Al; Hasaniyah, Nur (Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah, IAIN Kediri, 2024)
The dictionary is one of the important tools in language learning, including the Arabic language. An analysis of the components of this dictionary will provide a deeper understanding of its parts from the perspective of Dr. Ali Al-Qasimy. This study aims to analyze the components of the Saluni Wal Mutaradifat Wal Ma'ani Dictionary using a literature research method. The analysis results indicate that this dictionary still requires further improvements to reach the expected level of perfection. Nevertheless, it possesses adequate vocabulary completeness that can support vocabulary learning in the Arabic language, despite some components being incompletely fulfilled. A few enhancements and additions of specific features are needed for the Saluni Wal Mutaradifat Wal Ma'ani Dictionary to become a stronger resource for Arabic language learners. Although not perfect, this dictionary remains usable and beneficial for users in learning the Arabic language. This research solely conducted content analysis within the dictionary, hence it can still be developed further through subsequent studies such as testing effectiveness with quantitative studies by conducting direct field research.